2002
DOI: 10.1046/j.1365-2362.2002.01080.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acetylsalicylic acid on proliferation, apoptosis, and invasion of cyclooxygenase‐2 negative colon cancer cells

Abstract: Our findings reveal that ASA inhibits the proliferation and promotes apoptosis in the human colon cancer cell line SW480. Down-regulation of Bcl2 expression might represent a potential mechanism by which ASA induces apoptosis in this COX-2 negative colon cancer cell line. Our results also suggest that ASA decreases the invasive potential of these colon cancer cells. Decreased CEA content and CD44v6 expression and elevated nm23 expression may contribute to the effect of ASA on invasive potential of SW480 colon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 18 publications
3
39
0
Order By: Relevance
“…(9)], with a range of theories in circulation such as; cyclooxygenase (COX) inhibition (7,10), NF-κB inhibition (11)(12)(13), NF-κB activation (14,15), down-regulation of Bcl-2 expression (16,17), thus making the cells less resistant to the initiation of apoptosis, and down-regulation of c-Myc, cyclin D1, cyclin A and proliferating cell nuclear antigen (PCNA) (18), the intrinsic antioxidant activity of aspirin preventing double stranded DNA breaks (19), aspirin induces translocation of Bax to mitochondria (20), NSAIDSs up-regulate 15-lipoxygenase-1 expression (21), inhibition of cytosolic phospholipase A 2 expression (22), depletion of intracellular polyamines (23), increased Rac 1 expression (24), increased NSAID-activated gene (NAG-1) protein (25 and refs. therein), selection for microsatellite stability (26), and induction of the DNA mismatch repair (MMR) proteins hMLH1, hMSH2, hMSH6 and hPMS2 in DNA MMR proficient cells, which ultimately facilitates programmed cell death (27).…”
Section: Introductionmentioning
confidence: 99%
“…(9)], with a range of theories in circulation such as; cyclooxygenase (COX) inhibition (7,10), NF-κB inhibition (11)(12)(13), NF-κB activation (14,15), down-regulation of Bcl-2 expression (16,17), thus making the cells less resistant to the initiation of apoptosis, and down-regulation of c-Myc, cyclin D1, cyclin A and proliferating cell nuclear antigen (PCNA) (18), the intrinsic antioxidant activity of aspirin preventing double stranded DNA breaks (19), aspirin induces translocation of Bax to mitochondria (20), NSAIDSs up-regulate 15-lipoxygenase-1 expression (21), inhibition of cytosolic phospholipase A 2 expression (22), depletion of intracellular polyamines (23), increased Rac 1 expression (24), increased NSAID-activated gene (NAG-1) protein (25 and refs. therein), selection for microsatellite stability (26), and induction of the DNA mismatch repair (MMR) proteins hMLH1, hMSH2, hMSH6 and hPMS2 in DNA MMR proficient cells, which ultimately facilitates programmed cell death (27).…”
Section: Introductionmentioning
confidence: 99%
“…Bax and BCl-2 expression can be up and down-regulated respectively, in a dose-dependent fashion, (up to 10 mM) in SW480 cells incubated with aspirin . BCL-2 expression can be reduced by aspirin in SW480 cells (Yu et al, 2002) and can also suppress apoptosis in CRC cells (Jiang & Milner, 2003). Pretreating LNCap (human prostate) and CX-01 (colorectal carcinoma) cell lines with aspirin was found to enhance the capacity of tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) to intiate apoptosis, an effect -according to the authors -related to down regulation of BCL-2 gene expression resulting from the inhibition of NF-κB (of which BCL-2 is a known target) (K.M.…”
Section: Nsaids Signalling Pathways and Apoptosismentioning
confidence: 98%
“…NSAIDs can also up-regulate 15-lipoxygenase-1 (15-LOX-1) in CRC cells: NS-398 and sulindac sulfone both induced expression in the DLD-1 (COX-1 and COX-2 negative) cell line; significantly, inhibiting 15-LOX-1 blocked the induction of apoptosis (Shureiqi et al, 2000). With respect to characterisation of the pathway by which NSAID toxicity occurs, reports have been rather contradictory: in vitro studies have suggested that whilst aspirin and other NSAIDs can cause cell cycle arrest and inhibit CRC proliferation, this may, (Din et al, 2004;Elder et al, 1996;Piazza et al, 1995;Yu et al, 2002;Yu et al, 2003) or may not (Shiff et al, 1996;Smith et al, 2000) occur with the induction of apoptosis, or may occur as consequence a combination of activation of both apoptotic and necrotic 'pathways' . Notwithstanding the apparently contradictory reports, an absence of Bax expression in CRC cells has been found to abolish the apoptotic response to NSAIDs .…”
Section: Nsaids Signalling Pathways and Apoptosismentioning
confidence: 99%
“…This class of compounds exert anti-infl ammatory effects throughout the inhibition of cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2) leading to the inhibition of prostaglandin synthesis (Yu et al, 2002;Mahdi et al, 2006). The antiinflammatory and anti-nociceptive properties of extracts of willow family may be related to its phytochemicals such as salicin, myricetin, kaempferol, quercetin, rutin and luteolin (Qin & Sun, 2005;Nahrstedt et al, 2007).…”
Section: Introductionmentioning
confidence: 99%